2012
DOI: 10.1007/s00586-012-2462-1
|View full text |Cite
|
Sign up to set email alerts
|

Radiological study on disc degeneration of thoracolumbar burst fractures treated by percutaneous pedicle screw fixation

Abstract: Objective To examine disc degeneration at levels adjacent and next adjacent to the fractured vertebra and to analyses, if the disc degeneration is determined by the endplate fracture. Summary of background data Thoracolumbar burst fracture is one of the most common spinal injuries. The diagnostic (clinical and imaging) approach and treatment of a fractured vertebra is well established; however, some controversy remains. The associated disc degeneration is less well known after 9-12 months of the short segment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 17 publications
1
66
0
Order By: Relevance
“…Thus, altered nutrition supply of the endplate may be a causative factor in osteoporotic ASDD . Additionally, endplate damage, such as microfractures, creates abnormal stress distributions in the adjacent intervertebral disc, increasing the risk of internal disruption and disc degeneration . The current study showed a significant increase in endplate thickness and rate of calcification and significantly decreased in MVD and relative area of vascular buds in the Sham+PLF+V group.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Thus, altered nutrition supply of the endplate may be a causative factor in osteoporotic ASDD . Additionally, endplate damage, such as microfractures, creates abnormal stress distributions in the adjacent intervertebral disc, increasing the risk of internal disruption and disc degeneration . The current study showed a significant increase in endplate thickness and rate of calcification and significantly decreased in MVD and relative area of vascular buds in the Sham+PLF+V group.…”
Section: Discussionsupporting
confidence: 50%
“…(54,55) Additionally, endplate damage, such as microfractures, creates abnormal stress distributions in the adjacent intervertebral disc, increasing the risk of internal disruption and disc degeneration. (56)(57)(58) The current study showed a significant increase in endplate thickness and rate of calcification and significantly decreased in MVD and relative area of vascular buds in the ShamþPLFþV group. In addition, the parameters of the ASDD extent was significantly increased by addition of OVX.…”
Section: Discussionmentioning
confidence: 63%
“…Concerning the loss of adjacent disc height and disc degeneration after surgery, Wang et al [19] reported that disc degeneration usually occurs at the level adjacent to the fractured endplate of thoracolumbar burst fractures after implant removal in shortsegment pedicle screw fixation without augmentation. They also concluded that endplate fracture is strongly associated with disc degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…This group showed vertebral endplate lesions to be associated with disc degeneration, with larger lesions being associated with more severe disc degeneration . Furthermore, Wang et al found an increase in Pfirrmann degeneration grades in discs adjacent to the cranial fractured endplate 12 months post‐trauma (A3‐fractures), after removal of the pedicle screw instrumentation. No change was found in the caudal disc space or the levels next to the fractured vertebrae …”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, Wang et al found an increase in Pfirrmann degeneration grades in discs adjacent to the cranial fractured endplate 12 months post‐trauma (A3‐fractures), after removal of the pedicle screw instrumentation. No change was found in the caudal disc space or the levels next to the fractured vertebrae …”
Section: Discussionmentioning
confidence: 99%